Animal Models of Allergic Airways Disease: Where Are We and Where to Next?. Issue 12 (15th October 2014) - Chapman, David G.; Tully, Jane E.; Nolin, James D.; Janssen‐Heininger, Yvonne M.; Irvin, Charles G.
ABSTRACT In a complex inflammatory airways disease such as asthma, abnormalities in a plethora of molecular and cellular pathways ultimately culminate in characteristic impairments in respiratory function. The ability to study disease pathophysiology in the setting of a functioning immune and respiratory system therefore makes mouse models an invaluable tool in translational research. Despite the vast understanding of inflammatory airways diseases gained from mouse models to date, concern over the validity of mouse models continues to grow. Therefore the aim of this review is twofold; firstly, to evaluate mouse models of asthma in light of current clinical definitions, and secondly, to provide a framework by which mouse models can be continually refined so that they continue to stand at the forefront of translational science. Indeed, it is in viewing mouse models as a continual work in progress that we will be able to target our research to those patient populations in whom current therapies are insufficient. J. Cell. Biochem. 115: 2055–2064, 2014. © 2014 Wiley Periodicals, Inc.